PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG TANAMAN TRANSGENIK MELALUI EDUKASI ONLINE - Wahyuni, Febriana Dwi; Novianti, Titta; Saraswati, Henny; Seprianto, Seprianto (Jurnal Pengabdian Masyarakat AbdiMas, 2021)
Transgenic plants are genetically modified plants made by inserting one or a number of genes from other organisms, with the aim of obtaining superior and desirable new traits, such as resistance to drought stress, resistance to pests, resistance to herbicides. So far, there are still many people who are worried about the safety of transgenic plants that have been successfully marketed. Therefore, we strive to provide information based on existing references to increase public understanding of GM crops. The educational materials provided consisted of an introduction to plant breeding techniques and the purpose of genetic transformation in plants, gene cloning techniques and the transformation of target genes into plant genomes to produce transgenic plants and molecular techniques used to select transgenic plants which were delivered in the form of online seminars. via zoom and live streaming on youtube. The flow of activities is divided into two stages, namely material presentation and discussion. This activity is expected to increase knowledge about assembling techniques for transgenic plants as an effort to educate the public regarding the safety of transgenic plants. Keywords: biotechnology, cloning, GMOs, transgenic plants